Oral health status of hearing and speech-impaired schoolchildren in Erode district, Tamil Nadu - A cross-sectional study - S Kalaivani; Girish R Shavi; Shankar Shanmugam; Ranganath Sanga; Lalithambigai Gunasekaran; C Rahila (Wolters Kluwer Medknow Publications, 2021)
Background: Children with hearing and speech impairment are one of the important groups deprived of good oral health due to communication barriers. The chance of acquiring minimal information can significantly affect their personal as well as oral health. Aim: The present study was conducted to assess the oral health status among hearing and speech-impaired children in Erode. Materials and Methods: This cross-sectional descriptive study was conducted among hearing and speech-impaired children aged 7-14 years attending special schools at Erode, Tamil Nadu. A structured questionnaire written in vernacular language (Tamil) was used to obtain information on demographic details and oral hygiene practices. Then, oral examination was carried out and findings were recorded in the WHO Oral Health Assessment Form for Children, 2013. Descriptive statistics and Chi-square test were used for statistical analysis. Results: A total of 75 children were examined including 46 males (61%) and 29 females (39%). The common dental diseases found in the children were dental caries (65%) and gingival bleeding (47%). Most of the children (76%) required prompt treatment. Intervention urgency is higher among those children who have not visited a dentist before. Conclusion: The present study population has extensive dental treatment needs owing to communication difficulties and underutilization of dental care. The dental professionals along with the school authorities and voluntary agencies should reorganize the preventive as well as curative dental services so as to benefit the hearing and speech-impaired children.